Polymorphisms in the IL6 gene in Asian Indian families with premature coronary artery disease – The Indian Atherosclerosis Research Study - Maitra, Arindam; Shanker, Jayashree; Dash, Debabrata; John, Shibu; Sannappa, Prathima R.; Rao, Veena S.; Ramanna, Jayakumar K.; Kakkar, Vijay V. (Thrombosis and Haemostasis, 2008)
Inflammation plays a major role in coronary artery disease (CAD). We investigated the polymorphisms in the interleukin 6 (IL6) gene and their effect on the expression of acute-phase proteins in premature CAD in Asian Indian families. One hundred and ninety affected sibling pairs (ASPs) were genotyped for three tag single nucleotide polymorphisms (SNPs) in the IL6 gene for linkage analysis. We observed suggestive logarithm of odds (LOD) score for one SNP (rs2066992) in a subset of 62 ASPs with the age at onset less than 45 years (LOD score = 1.114, p = 0.011 in linkage analysis; pi = 0.55, p = 0.008 in identity by descent; LOD score = 1.06, p = 0.014 in quantitative trait locus for plasma levels of high sensitivity C-reactive protein, hsCRP). This was followed by sequencing of the promoter region and haplotype analysis in 46 probands and 40 controls. Five out of the eight previously reported promoter SNPs were found to be polymorphic (rs1800797, rs1800796, rs7802307, rs7802308, rs1800795). Two novel sequence variants were also found. One promoter haplotype (GGAAG) was detected with an odds ratio (OR) of 3.676 (p = 0.0017, 95% confidence interval [CI]: 1.68 – 8.045) and population attributable risk of 21.1% (95%CI: 9.2%-31.5%). The plasma levels of both hsCRP and fibrinogen exhibited significant association with these promoter SNP genotypes (p < 0.001). In conclusion, IL6 gene polymorphisms appear to be important genetic factors in premature CAD, and in the regulation of key atherogenic markers in Asian Indian families.
Keywords: Asian Indians; CAD; IL6; CRP; fibrinogen